An Open Source Toolbox for Integrating Freshwater Social-Ecological Indicators in Basin Management. Issue 1 (30th March 2020) - Shaad, Kashif; Alt, Howard
The Freshwater Health Index (FHI) toolbox is an open source software in C# developed to guide ecological management of freshwater systems. It provides functionality to calculate basin-level freshwater social-ecological indicators, with algorithms for selected indicators also integrated with support for processing geospatial datasets. The toolbox archives the data necessary for calculating the indicators and can serve as a collaborative platform in a basin by providing users with the ability to initiate, edit and share a common freshwater basin database. Now available at GitHub and through the FHI website, the FHI toolbox offers a convenient yet rigorous way for basin-level freshwater management to maintain continuity and reproducibility amid numerous indicators assessed for freshwater basins.